Managing student mobility during the COVID-19 Pandemic: An immobility turn in internationalized learning? - Cairns, D. (2022)
This article looked at the impact of the COVID-19 pandemic on the management of internationalized learning, and the disruption to the transitions to adulthood among students reliant upon the freedom to move within and between countries. We started by outlining the place of mobility in transitions, connected to debates about the ‘Mobility Turn,’ with particular relevance to developments in the European context, including the expansion of successive Erasmus student mobility programmes. Following the start of the pandemic, we hypothesize that we are now experiencing an ‘Immobility Turn’ in youth transitions, which, even if temporary, has the potential to disrupt personal and professional development of many young people in problematizing stays abroad at foreign universities. To explore this issue, we drew on evidence from Portugal, discussing issues including the measures taken by host institutions to maintain a safe environment and secure the integrity of educational courses for their international students, thus keeping open their mobile transition pathways. This research also enables us to illustrate the changes in the materiality of internationalized higher education that took place during the pandemic, and the challenges facing academic staff members. In conclusion, we look towards the future of mobile transitions, recognizing the important role played by staff members, and look towards future developments, including the heightened use of virtual mobility platforms for students with the potential to further transform the meaning of internationalized tertiary education.